STUDI PEMBINAAN AKHLAK PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER DI MTs HIDAYATUL MUBTADIIN SIDOHARJO - Asmadewi (UNISAN JURNAL, 2024)
This research examines the efforts made by extracurricular coaches in fostering the morals of students at MTs Hidayatul Mubtadiin. The problems discussed in this thesis include various forms of ROHIS extracurricular activities carried out at MTs Hidayatul Mubtadiin, the efforts made by the supervisors of ROHIS extracurricular activities in fostering the noble character of students at MTs Hidayatul Mubtadiin and factors supporting and inhibiting ROHIS extracurricular activities at MTs Hidayatul Mubtadiin Sidoharjo. To discuss the problems posed, data was collected in the field using observation, documentation and interview techniques. Sources of data obtained were the Head of Madrasah, Deputy Principal, supervisor of ROHIS extracurricular activities, Head of Administration and students. The collected data is then processed through three stages, namely data reduction, data display, and data leveraging, then conclusions are drawn and analyzed qualitatively. To examine the problems in this thesis, an interdisciplinary approach is used, namely the theological-normative approach, the pedagogical approach, the approach approach, and the sociological approach. After analyzing the data obtained, the results show that there are 11 forms of ROHIS extracurricular activities that were developed at MTs Hidayatul Mubtadiin and lead to efforts to foster students' morals. The efforts made by extracurricular activities in fostering students include efforts to increase and arouse religious beliefs, instill good social ethics in the family environment, community environment and madrasa environment and instill good habits in the form of discipline, responsibility, social relations and carrying out rituals.